Analysing the influence of the pandemic on crime patterns in North Macedonia - Kanevche, Aleksandra; Filiposka, Sonja; Mishev, Anastas (My University, 2022)
Reducing national crime rate is an extremely important, but also difficult problem. For solving it, it is necessary to discover patterns of its occurrence, the various factors that influence it and the connection between criminal actions, which can help forecast future events, especially violent crimes where the police should act immediately. However, some major events, such as the COVID-19 pandemic may significantly affect these models. Therefore, this paper focuses on analyzing the impact of the pandemic on the crime rates and patterns and the way the crime forecasting models are affected by these changes, using North Macedonia’s crime records as case study. The results show significant change in the rate and types of crimes during the pandemic period, when compared to the pre-pandemic period. Due to these changes in the crime patters, the crime forecasting models are also different, in terms of their accuracy and in terms of the importance of the input features that are used for the prediction.
Keywords: crime pattern, crime forecasting, pandemic correlation